PRACTICAL LAND GRADING BASED ON LEAST SQUARES. - Scaloppi, Edmar José [UNESP]; Willardson, Lyman S. [UNESP] (American Society of Civil Engineers (ASCE), 1986)
Practical methods for land grading design of a plane surface for rectangular and irregularly shaped fields based on a least squares analysis are presented. The least squares procedure leads to a system of three linear equations with three unknowns for determination of the best-fit plane. The equations can be solved by determinants (Cramer's rule) using a procedure capable of solution by many programmable calculators. The detailed computational process for determining the equation of the plane and a simple method to find the centroid location of an irregular field are also given. An illustrative example and design instructions are included to demonstrate the application of the design procedure.
Keywords: DRAINAGE; IRRIGATION; MATHEMATICAL MODELS; SOILS; LAND GRADING; AGRICULTURAL ENGINEERING